Introductory Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-805-X
ISBN 13: 978-0-13417-805-9

Chapter 2 - Section 2.2 - The Multiplication Property of Equality - Exercise Set - Page 130: 39



Work Step by Step

$-x-3=3$ First add 3 to both sides. $-x=3+3$ $-x=6$ Then multiply both sides by -1. $-x(-1)=6(-1)$ $x=-6$ Check the answer. -(-6)-3=3 6-3=3 3=3
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.